Geochemistry and Mineralogy of Ni-Co Laterite Deposits - Domènech, Cristina; Villanova-de-Benavent, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, entitled "Geochemistry and Mineralogy of Ni-Co Laterite Deposits", presents an updated overview of Ni-Co laterites as sources of Ni and Co but also of other metals of interest, such as Sc, PGE or REE. This collection is composed by researchers from different fields. The Special Issue starts with two general descriptions of previously unknown laterite deposits, a clay-type Ni-laterite deposit from Cuba and a magnesium silicate Ni-laterite deposit from the Philippines. It follows with four papers focusing on the occurrence of Co, Sc and other critical metals located in current tropical environments (the Dominican Republic, Venezuela and Brazil) as well as non-tropical environments (the Balkan peninsula, Spain and Chile). The three following papers deal with novel techniques or methodologies to improve the characterization of the Ni-laterite profiles, involving the use Al as a Sc proxy, water correction of in situ portable XRF analyses, and the study of hyperspectral data using quadrant scan. The next paper focuses on the silicification commonly observed, yet understudied, in some Ni-laterite profiles using oxygen and silicon isotopes. And finally, the last contribution examines the presence of unusual minerals (diamond, SiC) in Ni-laterite breccias.